Violência intrafamiliar : a compreensão de psicólogos que atendem em instituições crianças do sexo masculino, vítimas do abuso sexual - Pires Filho, Moacyr Ferreira (2007)
This study is based on reports given by psychologists working at several institutions and aims at understanding the impact of interfamily sexual abuse in victimized male children. The research is qualitative. Seven female psychologists were interviewed. In order to collect data, an interview guideline was followed individually with each participant. The interviews were transcribed and analyzed according to the Contents Analysis technique (MINAYO, 2004). It was observed that the suffering brought by the victimized children and their families, when faced with the main procedures at the institutions, which attend them, tend to put those children in a new situation of stress because they bring back the violence process suffered. It became evident the importance of the bond between the child and the psychologist so that he or she can have a more suitable approach to the problem. Family investment is also important since the psychological consequences become more or less difficult to be overcome depending on how the family reacts to the situation of abuse. Children who suffered sexual abuse usually present symptoms of post traumatic stress disorder and dissociative disorder . The psychological consequences seen from the interviews are: nightmares, night terror, depression, lowered self-esteem, autonomy impairment, fear of homosexuality, confusion regarding sexual orientation. In interpersonal relationships they show apathy, passivity, inconstant behavior, aggressive expression and sexual exacerbation, difficulty to create affective bonds and difficulties to express feelings. At school there is evidence of participation blunting with a social group, cognitive obstruction, which has influence on the learning process. We hope the present work would help understanding the subject studied and stimulate further research and interventions so that this kind of violence is confronted.